2021
DOI: 10.1155/2021/4694577
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cataract Surgery on Vision-Related Quality of Life and Psychological Distress in Monocular Patients

Abstract: Purpose. To determine the changes in vision-related quality of life and psychological distress after cataract surgery in monocular patients and to compared these with a control group of age- and gender-matched binocular patients. Methods. We enrolled 40 monocular patients and 40 binocular patients who underwent cataract surgery from August 2017 to December 2018. All participants undertook eye examinations and answered questionnaires (the National Eye Institute Visual Function Questionnaire, Self-rating Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Additional studies that have investigated patients undergoing cataract surgery in which there were no ocular diseases with the exception of cataracts have also reported finding a significantly improved VFQ-25 score [14,15]. The predictive factor for postoperative VR-QOL improvement has been reported to be a low pre-operative VR-QOL and the BCVA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies that have investigated patients undergoing cataract surgery in which there were no ocular diseases with the exception of cataracts have also reported finding a significantly improved VFQ-25 score [14,15]. The predictive factor for postoperative VR-QOL improvement has been reported to be a low pre-operative VR-QOL and the BCVA [14].…”
Section: Discussionmentioning
confidence: 99%
“…While there was only one study, to the best of the authors' knowledge, that reported longitudinal data on the impact of cataract surgery on GA, 15 however, there were a handful of studies that reported data on depressive symptoms previously, whose findings were comparable to that of ours. [6][7][8][9]11,14,15,[18][19][20][21][22][23] Compared to the general population in India, patients with untreated cataracts examined in this study were 9-fold as likely to suffer from depressive symptoms and 2-fold from GA. 1 As expected, the mean scores for depression and GA witnessed a significant drop post-surgery across all three groups. Restoration of vision post-surgery had the highest impact on both depressive and GA symptoms in the short-run (at 6 months), while regaining functional independence post-surgery seems to contribute to improved mental health symptoms at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that evaluated depression before and after cataract surgery thus far have revealed that cataract surgery positively affected depressive symptoms in adults. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] No longitudinal studies have looked at the impact of cataract surgery on psychological attributes among Indian adults. With one in seven Indians affected by mental disorders of varying severity and cataracts being the leading cause of reversible blindness in India, corrective cataract surgery may be an effective strategy for decreasing the burden of mental health disorders among those with VI in the country.…”
mentioning
confidence: 99%
“…Few studies, however, have investigated the experiences of patients undergoing only eye surgery [2,10,11]. The Only Eye Study 2 by Jones et al [2] explored the experience of only eye surgery patients by qualitative analysis of semi-structured interviews.…”
Section: Introductionmentioning
confidence: 99%